Capture of Mental States in Social Networks. A Philosophy of the Extended Mind - Gherab Martin, Karim (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2019)
This article analyzes how technology multinationals, and in particular those that are dedicated to social networks, are developing techniques to build mental metrics of users who browse the Internet in order to know their emotions, their feelings, their tastes, their phobias, and, ultimately, their psyche. Some simple examples of how these techniques can be implemented are shown. Specifically, we will focus on a very particular trait of the mental: intentionality.